THE DIFFERENCE BETWEEN INDIVIDUALS DOING SPORTS OR NOT IN TERMS OF THEIR STRESS COPING STYLES - TAZEGÜL, Ünsal (IJRDO- Journal of Educational Research, 2016)
In this study, it was aimed to analyze the difference between individuals doing sports or not interms of their stress coping styles. The target population of the study was created by thestudents of Istanbul Gelişim University while the sample of the study was selected by a totalof 121 students, 60 of them doing regularly sports and 61 of those not doing sports, whovoluntarily agreed to participate in the study. Stress coping styles of students have beenmeasured through Coping Styles of Stress Scale that was adapted in Turkish by Şahin andDurak. “The Kolmogorov-Smirnov Test” was applied in order to decide whether data hasnormal distribution and “Levene’s Test” was applied to test the homogeneity of variances andit is observed that data is homogeneous and has a normal distribution. Descriptive statisticsand one-sample t test was used to analyze the data. At the end of the study, it was determinedthat individuals doing sports' scores related to self-confidence and optimistic approach werehigher than those not doing sports. In addition, individuals not doing sports' scores related tosubmission and obedience were observed as higher than individuals doing sports.